Islamic Social Reporting Disclosure (ISRD) : Analisis Pengaruh Ukuran Perusahaan dan Usia Direksi terhadap Profitabilitas Sebagai Variabel Moderasi pada Perusahaan Teknologi Periode 2019-2022 - Zakaria, Ahmad; Sumarno, Ari Pitoyo; Handayani, Agustia (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
This study aims to examine the influence of firm size and board of directors' age on ISRD. Islamic Social Reporting (ISR) is a social reporting standard applied to Sharia-compliant companies, including those with Sharia securities. ISRD is not only intended for stakeholders but, most importantly, for Allah SWT, customers, employees, and the environment, as a form of social responsibility. This study was conducted on technology companies listed in the Sharia Securities List (DES) for the 2019-2022 period, with a total population of 38 companies. The research sample was selected using purposive sampling, resulting in 19 companies that met the criteria. Given the five-year research period, the total number of observational samples used in this study is 120. Data analysis was performed using EVIEWS software for hypothesis testing and Moderated Regression Analysis (MRA). The results indicate that firm size does not affect ISRD, whereas the board of directors' age has a positive influence on ISRD. Additionally, profitability is proven to strengthen the impact of firm size and board of directors' age on ISRD.